O trabalho escravo contemporâneo como fator de descumprimento da função social da propriedade rural - MELO, Herena Neves Maués Corrêa de (Universidade Federal do Pará, 2015)
This study aims to analyze the non fulfilment of the homestead social function linked to the reduction of the number of workers in a condition akin to slaves, considering that the Federal constitution of 1988 indicated the human being dignity fundamental for the democratic State of Right, as well as it emphasized, in the set of requirements for the fulfillment of the property social function, art. 186, the observance of laws that regulate the labor relations and the exploration in order to promote the proprietor’s and the workers’ well-beig. In this study, the homestead social function is analyzed as an element inherent to the recent concept of property right. Considering the property social function as structural to the property right, that is to say, the agrarian property right exists to fulfil a necessary function for the society. The inobservance of this social-functionality, drives the related right to its proper extinction, and it takes back from the State the obligation to protect the condition of proprietor of the one who does not fulfil. According to this, the expropriation of properties where the workers are in condition akin to slaves would be a suggestion to invigorate the dogma of the homestead right. Concerning to the property social function, it is necessary to understand the concept of this principle, selected by the Brazilian Political Letter in several articles. It is a plastic concept that can vary according to the objectives defined by the State as possibilities of environmental-economical-social development. So, the approach of this study has the objective to observe the humanity values in a detailed way, based on the Republican Letter, and focusing on the content of the property right and the human being’s dignity.